RobotX: development of surface vehicle's flying drone for augmented perception - Tai, Benjamin Joe Yew (Nanyang Technological University, 2025)
This abstract outlines the development of a competitive Unmanned Aerial Vehicle (UAV) designed and built for the RobotX 2024 Challenge.